"Complete the square" is one of the methods being applied to solve any kind of quadratic equation.

**Step 1 :**

First we have to check whether the coefficient of x² is 1 or not. If yes, we can proceed the second step, otherwise we have to divide the entire equation by the coefficient of x².

**Step 2 :**

Bring the constant term which we find on the left side to the right side.

**Step 3 : **

We have to add the square of half of the coefficient of "x" on both sides.

**Step 4 :**

Now the three terms on the left side will be in the form of a² + 2 a b + b² (or) a² - 2 ab + b².

**Step 5 :**

Then, we can write (a + b)² for a² + 2 a b + b² and (a- b)² for a² - 2 a b + b². Then we have to solve for x by simplification.

**Example 1 :**

Solve the quadratic equation x² + 6 x - 7 = 0 by completing the square method

**Solution:**

(x + 3)² = 16

x + 3 = √ 16

x + 3 = ± 4

x + 3 = 4 x = 1 |
x + 3 = - 4 x = -7 |

**Example 2 :**

Solve the quadratic equation x² + 3 x + 1 = 0 by completing the square method

**Solution:**

x² + 3 x + 1 = 0

x² + 3 x = -1

x² + 2 **x**** **(3/2) + (3/2)² = - 1 + (3/2)²

[x + (3/2)]² = - -1 + (9/4)

(x + (3/2))² = (9/4) - 1

(x + (3/2))² = (5/4)

(x + (3/2)) = √(5/4)

x + (3/2) = ± (√5/2)

x + (3/2) = (√5/2) x = (√5/2) - (3/2) x = (√5 - 3)/2 |
x + (3/2) = -(√5/2) x = -(√5/2) - (3/2) x = (-√5 - 3)/2 |

**Example 3 :**

Solve the quadratic equation 2 x² + 5 x - 3 = 0 by completing the square method

**Solution:**

2 x² + 5 x - 3 = 0

divide the whole equation by 2

x² + (5/2) x - (3/2) = 0

x² + (5/2) x = (3/2)

x² + 2 (5/2) x = (3/2)

x² + 2 x (5/2) + (5/2)² = (5/2)²+ (3/2)

(x + (5/2))² - (25/4)- (3/2) = 0

(x + (5/2))² = (25/4) + (3/2)

(x + (5/2))² = (25 + 6)/4

(x + (5/2))² = 31/4

x + (5/2) = √(31/4)

x + (5/2) = ± √31/2

x + (5/2) = √31/2 x = (√31/2) - (5/2) x = (√31 - 5)/2 |
x + (5/2) = -√31/2 x = (-√31/2) - (5/2) x = (- √31-5)/2 |

**Problem 4:**

Solve the quadratic equation 4 x² + 4 b x - (a² - b²) = 0 by completing the square method

**Solution:**

4 x² + 4 b x - (a² - b²) = 0

dividing the whole equation by 4,we get

x² + b x - (a² - b²)/4= 0

x = (a - b)/2 or x = (-a -b)/2

**Problem 5:**

Solve the quadratic equation x² - ( √3 + 1) x + √3 = 0 by completing the square method

**Solution:**

x² - ( √3 + 1) x + √3 = 0

x = -1 , -√3

We hope that the students would have understood the stuff and example problems explained on "Complete the square".

Apart from the stuff and example problems explained above, if you want to know more about "Complete the square", please click here

HTML Comment Box is loading comments...

**WORD PROBLEMS**

**HCF and LCM word problems**

**Word problems on simple equations **

**Word problems on linear equations **

**Word problems on quadratic equations**

**Area and perimeter word problems**

**Word problems on direct variation and inverse variation **

**Word problems on comparing rates**

**Converting customary units word problems **

**Converting metric units word problems**

**Word problems on simple interest**

**Word problems on compound interest**

**Word problems on types of angles **

**Complementary and supplementary angles word problems**

**Markup and markdown word problems **

**Word problems on mixed fractrions**

**One step equation word problems**

**Linear inequalities word problems**

**Ratio and proportion word problems**

**Word problems on sets and venn diagrams**

**Pythagorean theorem word problems**

**Percent of a number word problems**

**Word problems on constant speed**

**Word problems on average speed **

**Word problems on sum of the angles of a triangle is 180 degree**

**OTHER TOPICS **

**Time, speed and distance shortcuts**

**Ratio and proportion shortcuts**

**Domain and range of rational functions**

**Domain and range of rational functions with holes**

**Graphing rational functions with holes**

**Converting repeating decimals in to fractions**

**Decimal representation of rational numbers**

**Finding square root using long division**

**L.C.M method to solve time and work problems**

**Translating the word problems in to algebraic expressions**

**Remainder when 2 power 256 is divided by 17**

**Remainder when 17 power 23 is divided by 16**

**Sum of all three digit numbers divisible by 6**

**Sum of all three digit numbers divisible by 7**

**Sum of all three digit numbers divisible by 8**

**Sum of all three digit numbers formed using 1, 3, 4**

**Sum of all three four digit numbers formed with non zero digits**

**Sum of all three four digit numbers formed using 0, 1, 2, 3**

**Sum of all three four digit numbers formed using 1, 2, 5, 6**